ANALISIS PEMANFAATAN SUMBER BELAJAR PADA PEMBELAJARAN TEMATIK KELAS II DI MADRASAH IBTIDAIYAH AL-HASIB PAKIS KABUPATEN MALANG - Efiana Dwi Wulan Sari; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This research is a discusses the analysis of learning resources used in thematic learning for class II at MI Al-Hasib Pakis, Malang Regency. This study discusses what learning resources are used, how to use learning resources used and what factors underlie the use of learning resources in class II thematic learning at MI Al-Hasib Pakis. The use of learning resources in class II can be said to be quite good, because the teacher has made maximum use of learning resources. However, it can be said that madrasas still have shortcomings in the availability of their learning resources. With these obstacles, teachers use objects around students and the madrasa environment as learning resources. The purpose of this study is to find out what learning resources are used in class II and how teachers use these learning resources. This research is a descriptive qualitative research data collection using observation, interview, and documentation techniques. The data analysis used was condensation, data presentation, and continued with conclusion drawing. The results of this study are about how the use of learning resources in class II thematic learning at MI Al-Hasib Pakis